Regional structural change in Argentina (1996-2019): concepts, measurements and unequal trajectories over the business cycle - Niembro, Andrés Alberto (2024)
Fil: Niembro, Andrés Alberto. Universidad Nacional de Río Negro. Instituto de Estudios en Ciencia, Tecnología, Cultura y Desarrollo (UNRN-CITECDE). CONICET. Río Negro, Argentina.